Strengthening Class XII Competence for Covid-19 Products Through the Ignition Combustion Injection System Workshop: Penguatan Kompetensi Kelas XII Produk Covid-19 Melalui Workshop Sistem Injeksi Ignition Cumbution - Syarifudin Syarifudin; Faqih Fatkhurrozak; Firman Lukman Sanjaya; Riky Ardiyanto; Eflita Yohana (Universitas Lancang Kuning, 2023)
Class XII students of the TBSM Department, SMK Ma'Arif NU 01 Wanasari, Brebes Regency, are products of distance learning (online) due to the Covid-19 pandemic. Practicum learning in school workshops or industrial workshops ould not be carried out so students’s quality of competence is low. Therefore, this workshop-based PKM aims to increase the competence of participants, especially in the field of motorcycle injection systems. The PKM will be held in two stages, namely on November 28, 2022 (stage 1), and November 29, 2022 (stage 2). ThePKM technique prioritizes the SCL method and Small Discussion. PKM participants are class XII students with a total of 20 people. PKM stage 1 results in an increased understanding of the working principle of a 4-stroke motorbike by 95%. This success was achieved from the evaluation that was carried out in each presentation of the material. Success was also obtained at the 2nd stage of PKM. The material on the working principles and functions of the injection system components was well received by the participants. As many as 95% of the participants were able to re-explain the working principles and work functions of the motorcycle injection system components